Algoritmos Genéticos para Escalonamento de Processadores - Corrêa, Jan Mendonça; Melo, Alba Cristina (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2000: Anais do I Workshop em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad_estendido.2000.19138, 2000)
ln its generic formulation, processor scheduling is a NP-Complete problem. Many different approaches have been proposed to the scheduling problem and one of them is the use of Genetic Algorithms (GA). These algorithms work using an analogy with living beings, mimicking their ability to adapt to the environment. The aim of this paper is to present a tentative of classification of GAbased processor schedulers and describe some of the results achieved and some aspects of GA that can interfere with the quality of the results.